Photo‐Effect on Ion Transport in Mixed Cation and Halide Perovskites and Implications for Photo‐Demixing. (10th November 2020) - Kim, Gee Yeong; Senocrate, Alessandro; Wang, Ya‐Ru; Moia, Davide; Maier, Joachim
Abstract: Lead halide perovskites are considered to be most promising photovoltaic materials. Highest efficiency and improved stability of perovskite solar cells have been achieved by using cation and anion mixtures. Experimental information on electronic and ionic charge carriers is key to evaluate device performance, as well as processes of photo‐decomposition and photo‐demixing which are observed in these materials. Here, we measure ionic and electronic transport properties and investigate various cation and anion substitutions with a special eye on their photo‐ionic effect, following our previous study on CH3 NH3 PbI3, where we found that light enhances not only electronic but also ionic conductivities. We find that this phenomenon is very sensitive to the nature of the halide, while the cationic substitutions are less relevant. Based on the observation that the ionic conductivity enhancement found for iodide perovskites is significantly weakened by bromide substitution, we provide a chemical rationale for the photo‐demixing in mixed halide compositions. Abstract : The photo‐effect on ion conduction in mixed cation and halide perovskites is studied. Unlike A‐site substitution, anion replacement is of great influence. In I‐Br mixtures the differences in hole localization and defect formation favor (reversible) photo‐demixing (the situation in the right part is simplified as the interstitial neutral iodine is further stabilized by ionic rearrangement, and the hole in the bromide is delocalized over several regular anions).